Greedy Based Radio Resource Allocation Algorithm with Sectoring Scheme in D2D Underlaying Communication - Putu Riyana Paramita; Nachwan Mufti Adriansyah; Vinsensius Sigit Widhi Prabowo (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2020)
D2D communication is a communication that allows users to communicate without passing through the Base Station (BS). The D2D Underlaying communication system can use the same Resource Block (RB) as the Cellular User Equipment (CUE). Implementing this communication system can ease the burden on BS and can transmit data with higher throughput in low power. However, using RB simultaneously can cause interference and therefore an RB allocation scheme is needed. The algorithm used in the scheduling process of the uplink RB owned by CUE to the D2D pair is the joint greedy algorithm with sectoring scheme. This work used a scenario where the value of the D2D pair are varied. The parameters measured in this simulation were sum-rate, spectral efficiency and fairness. The simulation results show that the joint greedy with sectoring allocation scheme has good energy efficiency and spectral efficiency values of 6.063× 106 bps/watt and 16.982 bps/Hz. On the other hand, the D2D fairness value in the joint greedy with sectoring allocation scheme is 0.886.